Multiple Benefits of Plasmid-Mediated Quinolone Resistance Determinants in Klebsiella pneumoniae ST11 High-Risk Clone and Recently Emerging ST307 Clone - Domokos, Judit; Damjanova, Ivelina; Kristof, Katalin; Ligeti, Balazs; Kocsis, Bela; Szabo, Dora (Frontiers in Microbiology, 2019)
International high-risk clones of Klebsiella pneumoniae are among the most common nosocomial pathogens. Increased diversity of plasmid-encoded antimicrobial resistance genes facilitates spread of these clones causing significant therapeutic difficulties. The purpose of our study was to investigate fluoroquinolone resistance in extended-spectrum beta-lactamase (ESBL)-producing strains, including four K. pneumoniae and a single K. oxytoca, isolated from blood cultures in Hungary. Whole-genome sequencing and molecular typing including multilocus sequence typing (MLST) and pulsed-field gel electrophoresis (PFGE) were performed in selected strains. Gene expression of plasmid-mediated quinolone resistance determinants (PMQR) was investigated by quantitative-PCR. MLST revealed that three K. pneumoniae strains belonged to ST11 and one to ST307 whereas K. oxytoca belonged to ST52. The isolates harbored different β-lactamase genes however, all K. pneumoniae uniformly carried blaCTX-M-15. The K. pneumoniae isolates exhibited resistance to fluoroquinolones and carried various PMQR genes namely, two ST11 strains harboured qnrB4, the ST307 strain harboured qnrB1 and all K. pneumoniae harboured oqxAB efflux pump. Levofloxacin and moxifloxacin MIC values of K. pneumoniae ST11 and ST307 clones correlated with qnr and oqxAB expression levels. The qnrA1 carrying K. oxytoca ST52 exhibited reduced susceptibility to fluoroquinolones. The maintained expression of qnr genes in parallel with chromosomal mutations indicate an additional protective role of Qnr proteins that can support dissemination of high-risk clones. During development of high-level fluoroquinolone resistance, high-risk clones retain fitness thus, enabling them for dissemination in hospital environment. Based on our knowledge this is the first report of ST307 clone in Hungary, that is emerging as a potential high-risk clone worldwide. High-level fluoroquinolone resistance in parallel with upregulated PMQR gene expression are linked to high-risk K. pneumoniae clones.